Communication in clinical practice: critical success factors for ESL students : a thesis completed in fulfilment of the requirements for the degree of Master of Philosophy at Massey University, Palmerston North - Eyre, Janet Mary (Massey University, 2010)
This study investigates the factors most likely to support effective communication in clinical placements for ESL nursing students in New Zealand. The experiences of ESL students as they complete a clinical placement are examined and compared with data from the students‟ clinical lecturers and preceptors. Data for the study was collected through interviews with individual students before, during and after their Transition to Practice placement. Interviews were also held with two of the students‟ preceptors, and a focus group was held with clinical lecturers who had experience of working with ESL students. Results from the study underline the importance of facilitating students‟ entry to the placement community of practice, and access to its interactions. A number of factors supported or inhibited students‟ participation and learning within the placement community. The study identified two critical factors intrinsic to the student, and two extrinsic to the student. Intrinsic factors included the student‟s proficiency with English language: in particular, the sophisticated sociopragmatic language skills used by nurses in their daily interactions. The student‟s use of learning strategies, including the proactive approach best suited to learning on placement, was also critical. Extrinsic factors likely to support the student‟s integration within the community of practice were the quality of the preceptor, in terms of attitude to and training for the preceptoring role, and the tone of the placement environment. The major outcomes of this study point to the importance of providing direct instruction for ESL students in the kinds of language and learning styles required for placement. There are also implications for the selection and training of preceptors and for the placing of students in appropriate clinical environments. The study concludes with suggestions for a specific communication programme for ESL students.
Keywords: Nursing training; Language skills; Fields of Research::320000 Medical and Health Sciences::321100 Nursing